Miniaturized planar filters for UWB application - Lau, Yizhang. (2012)
An ultra-wideband (UWB) bandpass filter using a multiple mode resonator (MMR) with a fractional bandwidth (FBW) of more than 100% is designed and demonstrated. There are several novels on how to improve a MMR design like using aperture-Backed PCML and Capacitive-Ended Interdigital Coupled lines. In this project, a microstrip stub-loaded dual-mode resonator doublets design is proposed. The doublet consists of two parallel but oppositely arranged stub-loaded resonators, and has a significantly widened passband. A final optimized UWB filter is designed by cascading three doublets, and eight transmission poles are obtained in its passband. The filter has a passband covering 3.3- 10.0GHz, and exhibits sharp attenuations near its passband. This project will be using Sonnet version 13.55 for full wave simulation. The substrate material used is RT/Duroid 6010 with dielectric value 10.8.